2013
DOI: 10.1371/journal.pone.0078114
|View full text |Cite|
|
Sign up to set email alerts
|

Re-Examination of Globally Flat Space-Time

Abstract: In the following, we offer a novel approach to modeling the observed effects currently attributed to the theoretical concepts of “dark energy,” “dark matter,” and “dark flow.” Instead of assuming the existence of these theoretical concepts, we take an alternative route and choose to redefine what we consider to be inertial motion as well as what constitutes an inertial frame of reference in flat space-time. We adopt none of the features of our current cosmological models except for the requirement that special… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 104 publications
0
21
0
Order By: Relevance
“…It is worth noting that the original paper of Weyl showed that the cylinder solution is diffeomorphic to a Schwarzschild's solution. In this process the metric does not lose its asymptotes as shown in (Weyl 1917;Rosen 1949;Zipoy 1966) and is also asymptotically flat (Weyl 1917;Rosen 1949;Zipoy 1966;Gautreau, Hoffman and Armenti 1972;Stephani et al 2003). This is a fine example of the equivalence problem in GR: How do we know that two solutions of Einstein's equations, written in different coordinates, do not describe the same gravitational field?…”
Section: Weyl's Gravitational Fieldmentioning
confidence: 78%
See 2 more Smart Citations
“…It is worth noting that the original paper of Weyl showed that the cylinder solution is diffeomorphic to a Schwarzschild's solution. In this process the metric does not lose its asymptotes as shown in (Weyl 1917;Rosen 1949;Zipoy 1966) and is also asymptotically flat (Weyl 1917;Rosen 1949;Zipoy 1966;Gautreau, Hoffman and Armenti 1972;Stephani et al 2003). This is a fine example of the equivalence problem in GR: How do we know that two solutions of Einstein's equations, written in different coordinates, do not describe the same gravitational field?…”
Section: Weyl's Gravitational Fieldmentioning
confidence: 78%
“…In this ⋆ E-mail:abraao.capistrano@unila.edu.br † E-mail:roque@ci.ufbp.br ‡ E-mail:rafaelsvalada@ulbra.edu.br respect, we use the Weyl metric that describes a cylindrical symmetry, motivated mainly on the fact that the solar system has an axial symmetry. From the geometrical point of view the Weyl cylindrically symmetric solution is diffeomorphic to the Schwarzschild solution and also is asymptotically flat as shown in (Weyl 1917;Rosen 1949;Zipoy 1966;Gautreau, Hoffman and Armenti 1972;Stephani et al 2003). For applications in astrophysics, the Weyl metric is fundamentally relevant as well as several non-asymptotically flat metrics, for instance, in the study of physics of black-holes, stellar evolution and galaxies as well as several studies of relativistic effects on solar system scale (Gutiérrez-Piñeres, González and Quevedo 2013;González, Gutiérrez-Piñeres and Ospina 2008;Katz, Bicák and Lynden-Bell 1999;Vogt and Letelier 2008;Ujevic andLetelier 2004, 2007;Sitarski 1983;Roberts 1987).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, Ref. 43 takes the Milky Way itself to constitute one of these new inertial frames with the center of the Milky Way in the direction of Sagittarius A* constituting the center of the inertial reference frame relevant for observers in our Solar System. In other words, it is assumed in this model that at the center of our galaxy there exists an inertial center and not a supermassive black hole (for recent tension with our current understanding of black hole formation, see Refs.…”
Section: Resultsmentioning
confidence: 99%
“…Since the explanation of the perihelion advance of Mercury by Einstein in 1915 as an application of general Relativity (GR), it has been considered one of the fundamental laboratories for testing extensions of standard GR and other gravitational models such as e.g, the modification of newtonian Dynamics (MOND) [2], Kaluza-Klein five-dimensional gravity [3], Yukawa-like Modified Gravity [4], Horava-Lifshitz gravity [5], brane-world models and variants [6][7][8][9][10][11][12], the parametric post-newtonian (PPN) framework and beyond, and approaches in the weak field/slow motion limits [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. As largely known, in GR, the coordinate systems are overall physically equivalents and to obtain new prospects on applications in astrophysics, the diffeomorphic a e-mail: abecapistrano@gmail.com b e-mail: paola.seidel@gmail.com c e-mail: cabral@uft.edu.br transformations cannot be allowed to happen.…”
Section: Introductionmentioning
confidence: 99%